Alternate bearing in fruit trees: fruit presence induces polar auxin transport in citrus and olive stem and represses IAA release from the bud. (21st December 2020) - Haim, Dor; Shalom, Liron; Simhon, Yasmin; Shlizerman, Lyudmila; Kamara, Itzhak; Morozov, Michael; Albacete, Alfonso; Rivero, Rosa M; Sadka, Avi
Abstract: In many fruit trees, heavy fruit load in one year reduces flowering in the following year, creating a biennial fluctuation in yield termed alternate bearing (AB). In subtropical trees, where flowering induction is mostly governed by the accumulation of chilling hours, fruit load is thought to generate a signal (AB signal) that blocks the perception of cold induction. Fruit removal during a heavy-fruit-load year is effective at inducing flowering only if performed one to a few months before the onset of the flowering induction period. We previously showed that following fruit removal, the content of the auxin indoleacetic acid (IAA) in citrus buds is reduced, suggesting that the hormone plays a role in the AB signal. Here, we demonstrate that fruit presence generates relatively strong polar auxin transport in citrus and olive stems. Upon fruit removal, polar auxin transport is reduced and allows auxin release from the bud. Furthermore, using immunolocalization, hormone, and gene expression analyses, we show that in citrus, IAA level in the bud and specifically in the apical meristem is reduced upon fruit removal. Overall, our data provide support for the notion that fruit presence generates an auxin signal in the bud, which may affect flowering induction. Abstract : Heavy fruit load can reduce flowering intensity the following year. Fruit presence, inducing polar auxin transport in stems and inhibiting auxin release from buds, may act as a fruit-load signal.